Induksi Tunas Tanaman Cendana (Santalum album L.) dengan Perlakuan GA3 secara In Vitro - EKA CHRISTY WAKANNO; RINDANG DWIYANI; ANAK AGUNG MADE ASTININGSIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Shoot Induction of Sandalwood (Santalum album L.) With GA3 Treatment In Vitro Sandalwood (Santalum album L.) is a woody plant with high economic value whose population is decreasing due to overexploitation. Propagation of sandalwood generatively and conventionally has been carried out but the success rate is still low due to the difficulty of obtaining quality adult individuals. This study aims to find the best concentration of GA3 in inducing sandalwood shoots in vitro. This research used Completely Randomized Design with 5 levels of treatment concentration of GA3 hormone, E0: WPM without GA3 (control), E1: WPM + 1 ppm GA3, E2: WPM + 2 ppm GA3, E3: WPM + 3 ppm GA3, E4: WPM + 4 ppm GA3. The results showed that the addition of GA3 concentration succeeded in inducing sandalwood shoots. The best 1 ppm GA3 for the variable when the fastest shoots were formed, which was 2.6 (DAT), and the variable number of shoots was (10). The best GA3 concentration of 2 ppm was on the number of explants that grew shoots (2.4), the percentage of explants sprouted (0.2%) and shoot length (1cm). GA3 1 ppm and 2 ppm succeeded in growing leaves.